Aurora kinase A is superior to Ki67 as a prognostic indicator of survival in neuroblastoma. Issue 3 (12th December 2014) - Ramani, Pramila; Nash, Rachel; Rogers, Chris A
<x xml:space="preserve">Abstract</x> Aims To compare the expression and prognostic value of the cell cycle markers Aurora kinase A (AURKA) and Ki67 in neuroblastoma, because AURKA expression levels have greater prognostic significance than those of Ki67 in some cancers. Methods and results Eighty‐eight neuroblastomas were immunostained with anti‐AURKA and Ki67 antibodies. Digitally scanned slides were scored using imaging analysis software. Median AURKA and Ki67 proliferation indices (PIs) were 1.5% and 26%, respectively. Higher than median AURKA and Ki67 levels were detected in the neuroblastomas from patients belonging to the high‐risk group, those with MYCN amplification, and those with unfavourable pathology, including a high mitosis–karyorrhexis index (MKI). High AURKA and Ki67 levels were significantly associated with shorter overall survival (OS) and event‐free survival (EFS) in univariate analyses. In multivariate analyses, high AURKA level was associated with significantly shorter OS and EFS, independently of risk group, and of MYCN amplification and MKI. High Ki67 level was not associated with shorter OS or EFS after adjustment for risk group or MYCN amplification and MKI. Conclusions High AURKA and Ki67 levels were associated with adverse prognostic factors and shorter survival, but AURKA provides more valuable prognostic information than Ki67 in neuroblastoma.